Rbies virus G-protein을 이용한 유전자 재조합 백신의 개발 - 이일섭 (The Graduate School, Ajou University, 2007)
This research was carried out to know the possibility of recombinant Rabies vaccine which had been introduced G-protein gene of rabies virus into adenovirus. The total RNA was extracted from the Rabies virus, ERA strain which had been cultivated at primary porcine kidney cell, and cDNA was synthesized. The primers for amplifying the whole G-protein were prepared and got the 1,570bp G-protein gene from PCR. The obtained G-protein was cut with restriction endonuclease, and inserted to adenovirus cosmid vector. This vector again inserted recombinant adenovirus cosmid vector with adenovirus genome DNA-TPC gene into 293 cells. The target protein was proven by RT-PCR, and western blot analysis, and named as AdenoERA-gp Recombinant virus. Conclusively, this AdenoERA-gp Recombinant virus may be effective as the recombinant rabies vaccine, and helpful to study for genetic research of rabies virus.
학위논문(석사)--아주대학교 일반대학원 :생명과학과,2007.2
Keywords: rabiesvirus; G-protein; adenovirus; recombinantvirus